2016
DOI: 10.18869/acadpub.jafm.68.228.24192
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effect on Mixed Convection Boundary Layer Flow of a Viscoelastic Fluid over a Horizontal Circular Cylinder with Constant Heat Flux

Abstract: In the present article, radiation effect on mixed convection boundary layer flow of a viscoelastic fluid over a horizontal circular cylinder with constant heat flux has been numerically analyzed. The governing boundary layer equations are transformed to dimensionless nonlinear partial differential equations. The equations are solved numerically by using Keller-box method. The computed results are in excellent agreement with the previous studies. Skin friction coefficient and Nusselt number are emphasized speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In addition to exhibiting both viscosity and elasticity, one category of non-Newtonian fluids with dual effect features is viscoelastic fluid (i.e., heat transfer reduction and drag reduction properties) 14 , which contributes to a wide range of applications in the polymer industry. Manufacture of paper, fibre glass, dyes, films, extraction processes, copper wire thinning and hardening, synthetic fibre and plastic film processing, drawing of plastic sheet, cooling of metallic chips, and food processing are all included in this 15 . In the process engineering of oil reservoirs, bio-engineering, the chemical industry, and nuclear technology, viscoelastic fluid is also crucial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to exhibiting both viscosity and elasticity, one category of non-Newtonian fluids with dual effect features is viscoelastic fluid (i.e., heat transfer reduction and drag reduction properties) 14 , which contributes to a wide range of applications in the polymer industry. Manufacture of paper, fibre glass, dyes, films, extraction processes, copper wire thinning and hardening, synthetic fibre and plastic film processing, drawing of plastic sheet, cooling of metallic chips, and food processing are all included in this 15 . In the process engineering of oil reservoirs, bio-engineering, the chemical industry, and nuclear technology, viscoelastic fluid is also crucial.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that a reduction in heat transfer processes results from an increase in the radiation parameter. Many studies, like Raja et al 7 , Datti et al 11 , and Ahmad et al 15 , have considered the impact of radiant heat on boundary layer flow induced by a nonlinearly stretching sheet because of its significance in controlling and maintaining the system's temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They solved the equations using the finite difference method, which they claimed was more accurate. Furthermore, Ahmad et al, [7] used KBM to investigate the flow of viscoelastic fluid across HCC. The authors have incorporated the radiation effect into the fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The study of non-Newtonian fluid fascinates researchers due to daily life significance in, and pastes, paints, biological fluids, motor oils, mechanical procedures, and complex mixtures. [20][21][22] Recently, many experts have been reported to analyze the dynamics of non-Newtonian fluids like tangent hyperbolic, 23,24 third grade, 25,26 Casson fluid, 27,28 power law nanofluid, 29,30 viscoelastic fluid, 31 and micropolar fluid. 32 The inherent difficulty in the solution of such problems due to the nonlinearity associated with convective terms in the formulation has been addressed by employing various numerical approaches such as finite difference (FD), finite volume (FV), boundary element (BE), and finite element (FE).…”
Section: Introductionmentioning
confidence: 99%
“…Rout et al 19 discussed the effects of chemical reactions on micropolar fluids with transverse magnetic field and wall temperature. The study of non‐Newtonian fluid fascinates researchers due to daily life significance in, and pastes, paints, biological fluids, motor oils, mechanical procedures, and complex mixtures 20–22 . Recently, many experts have been reported to analyze the dynamics of non‐Newtonian fluids like tangent hyperbolic, 23,24 third grade, 25,26 Casson fluid, 27,28 power law nanofluid, 29,30 viscoelastic fluid, 31 and micropolar fluid 32 …”
Section: Introductionmentioning
confidence: 99%